EMPOWERMENT OF THE TOURISM ACTIVISTS GROUP ((KOMPEPAR) IN DEVELOPMENT OF SUKAGEURI VIEW TOURISM DESTINATION IN KUNINGAN REGENCY - Ine Mariane; Imas Sumiati; NR. Ruyani (Pasundan International of Community Services Journal (PICS-J), 2020)
The main problem faced by the Tourism Activists Group (KOMPEPAR) in Sukageuri View Kuningan Regency is that a policy network has not yet been formed to form partnerships in developing tourist destinations in the region, due to lack of communication skills, resources and capital. The purpose of this community service is to guide the KOMPEPAR to communication knowledge in exploring existing tourism potential with the resources needed to build a policy network through community, government, and industrial / business partnerships needed to develop the existing tourism potential. The methodology for community service is divided into 3 (three), namely observation, training and simulation. The results of the dedication show that KOMPEPAR empowerment in developing tourist destinations in Sukageuri View Kuningan District requires a policy network that is by building partnerships / cooperation with various parties (public private partnership) both the government (Cisantana village officials and the Office of Youth, Sports, and Tourism (DISPORAPAR) Kuningan Regency, community tourism activist group (KOMPEPAR) Sukageuri View, as well as business / private sector including PLN Cikijing and West Java International Airport (BIJB) to strengthen synergy in promoting tourism and Kuningan's creative economy Impact on the community arising from the development of destinations This tour is quite good, which can increase daily income to meet their needs by conducting a creative economy in the area around the tourist attractions so that the community's economy becomes better, the level of people's welfare increases